The Technology Transfer from Europe to China in the 17th-18th Centuries: Non-Invasive On-Site XRF and Raman Analyses of Chinese Qing Dynasty Enameled Masterpieces Made Using European Ingredients/Recipes - Colomban, Philippe; Gironda, Michele; Vangu, Divine; Kirmizi, Burcu; Zhao, Bing; Cochet, Vincent (MDPI, 2021)
Two masterpieces of the Qing Dynasty (1644-1912 CE), one in gilded brass (incense burner) decorated with cloisonne enamels stylistically attributed to the end of the Kangxi Emperor's reign, the other in gold (ewer offered by Napoleon III to the Empress as a birthday present), decorated with both cloisonne and painted enamels bearing the mark of the Qianlong Emperor, were non-invasively studied by optical microscopy, Raman microspectroscopy and X-ray microfluorescence spectroscopy (point measurements and mapping) implemented on-site with mobile instruments. The elemental compositions of the metal substrates and enamels are compared. XRF point measurements and mappings support the identification of the coloring phases and elements obtained by Raman microspectroscopy. Attention was paid to the white (opacifier), blue, yellow, green, and red areas. The demonstration of arsenic-based phases (e.g., lead arsenate apatite) in the blue areas of the ewer, free of manganese, proves the use of cobalt imported from Europe. The high level of potassium confirms the use of smalt as the cobalt source. On the other hand, the significant manganese level indicates the use of Asian cobalt ores for the enamels of the incense burner. The very limited use of the lead pyrochlore pigment (European Naples yellow recipes) in the yellow and soft green cloisonne enamels of the Kangxi incense burner, as well as the use of traditional Chinese recipes for other colors (white, turquoise, dark green, red), reinforces the pioneering character of this object in technical terms at the 17th-18th century turn. The low level of lead in the cloisonne enamels of the incense burner may also be related to the use of European recipes. On the contrary, the Qianlong ewer displays all the enameling techniques imported from Europe to obtain a painted decoration of exceptional quality with the use of complex lead pyrochlore pigments, with or without addition of zinc, as well as cassiterite opacifier.
Keywords: painted enamels; cloisonne; gold alloy; blue; yellow; green; white; China; Qing Dynasty; spectroscopy; composition; BLUE-AND-WHITE; COLOR-GENERATING MECHANISM; SCATTERING FEATURES; LIMOGES ENAMELS; ANCIENT GLASSES; COBALT SOURCES; IDENTIFICATION; PORCELAIN; GLAZES; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics